2014
DOI: 10.1111/bph.12798
|View full text |Cite
|
Sign up to set email alerts
|

Revolution in GPCR signalling: opioid receptor heteromers as novel therapeutic targets: IUPHAR Review 10

Abstract: GPCRs can interact with each other to form homomers or heteromers. Homomers involve interactions with the same receptor type while heteromers involve interactions between two different GPCRs. These receptor–receptor interactions modulate not only the binding but also the signalling and trafficking properties of individual receptors. Opioid receptor heteromerization has been extensively investigated with the objective of identifying novel therapeutic targets that are as potent as morphine but without the side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 121 publications
(277 reference statements)
1
66
1
Order By: Relevance
“…Interestingly, in the above studies μ‐ORs were found to crystallize as dimers . Largely based on previous experiments applying resonance energy transfer methods, these findings support the hypothesis that μ‐ORs might form homodimers . However, the nanoscale organization and dynamics of μ‐ORs on the surface of living cells remain largely unknown, mostly due to technical limitations of conventional methods.…”
Section: Introductionsupporting
confidence: 71%
“…Interestingly, in the above studies μ‐ORs were found to crystallize as dimers . Largely based on previous experiments applying resonance energy transfer methods, these findings support the hypothesis that μ‐ORs might form homodimers . However, the nanoscale organization and dynamics of μ‐ORs on the surface of living cells remain largely unknown, mostly due to technical limitations of conventional methods.…”
Section: Introductionsupporting
confidence: 71%
“…46,83 Further, the impact of a 5-HT 2A R:5-HT 2C R protein complex on neuronal firing is not known and it is wholly possible that the biochemical, signaling, and pharmacological properties of the protein complex diverge from that of the single receptor, although this is a controversial and active research topic. 8487 Thus, while future research is required to tease apart the relative role of these two GPCRs within the same neurons versus interacting neurons in the mPFC, altered firing of GABA neurons which colocalize the 5-HT 2A R and 5-HT 2C R may dysregulate pyramidal outflow to drive motor impulsivity. The fact that systemic administration of 5-HT 2A R and the 5-HT 2C R ligands oppositionally control motor impulsivity 9,1120,2226 (and other behaviors) 88 adds further impetus to disentangling the mechanisms through which these receptors control neuronal output to mediate behaviors that contribute to chronic health disorders ( e.g ., drug addiction, attention deficit disorder, autism, and obesity/binge eating disorder).…”
Section: Resultsmentioning
confidence: 99%
“…The concept has now extended to rhodopsin-like class A GPCRs. As extensively reviewed recently, receptor heterooligomers are independent entities with distinct properties and regulation (Fujita et al, 2014(Fujita et al, , 2015Gomes et al, 2016).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%